2016
DOI: 10.1007/s11224-016-0782-1
|View full text |Cite
|
Sign up to set email alerts
|

At sixes and sevens, and eights, and nines: schwarzites p 3, p = 7, 8, 9

Abstract: Examples are given of vertex and/or face-transitive p 3 (p = 7, 8, 9) tilings of periodic minimal surfaces. Infinite families of tilings, including aperiodic structures, are readily derived from some of these. They are of particular interest for theoretical studies of potential carbon allotropes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The schwarzites reported here coincide in part with those in an earlier report [43], which led to this more comprehensive study. Nevertheless, most of the nets reported here are novel, but how many have we missed?…”
Section: Closing Remarkssupporting
confidence: 89%
See 3 more Smart Citations
“…The schwarzites reported here coincide in part with those in an earlier report [43], which led to this more comprehensive study. Nevertheless, most of the nets reported here are novel, but how many have we missed?…”
Section: Closing Remarkssupporting
confidence: 89%
“…As discussed above, the transitivity of these (7, 3) e-nets can be inferred from their tilings of H 2 , illustrated in figure 6. All e-net ( We believe that most of these structures were previously unknown, though some have been reported in a previous paper [43]. A notable exception is the kgn net [47].…”
Section: (A) (7 3) Schwarzitesmentioning
confidence: 84%
See 2 more Smart Citations
“…To verify the construction strategy and extend the relationship between G minimal surface and adsorption properties, herein we presented a new gyroidal MOF, [Cu 3 (IP-POH) 2 ]·NO 3 ·9H 2 O, namely, SCNU-1 (SCNU = South China Normal University), under solvothermal conditions by mixing Cu­(NO 3 ) 2 with 4-(1H-imidazo­[4,5- f ]­[1,10]­phenanthrolin-2-yl)­phenol (HIP-POH; Scheme S1). Single crystal structural analysis revealed that SCNU-1 is composed of two interpenetrating utc networks, which to the best of our knowledge is the first example found in the real structure, with opposite helical channels. This rare gyroidal MOF also showed high thermal stability (>773 K) and excellent water and chemical stabilities.…”
mentioning
confidence: 70%